Literasi Visual terkait Personal Hygiene dan Implikasinya terhadap Praktik Kebersihan Diri pada Masyarakat Pedesaan - Muhammad Ridha Afdhal; Marhawati, Marhawati; Salam, Jumhur; Hamid, Fatmawati; Mayasari, Eka (Yayasan Pendidikan Penelitian Pengabdian Algero, 2026)
Sanitation and personal hygiene remain critical public health concerns in rural communities, particularly in relation to health literacy and the adoption of preventive behaviors. This study aimed to analyze the level of understanding of personal hygiene symbols and its association with personal hygiene practices among residents of Desa Pabudunkang, South Bontonompo District, Gowa Regency. A quantitative survey design was employed involving 213 respondents selected through stratified random sampling. Data were collected using a structured questionnaire and analyzed using univariate and bivariate approaches to examine variable distribution and inter-variable relationships. The findings indicate that most respondents demonstrated good comprehension of personal hygiene symbols and consistently practiced hygiene behaviors in daily life. A significant association was identified between symbol comprehension and hygiene practices, suggesting that the ability to interpret visual health messages contributes to the adoption of clean and healthy behaviors. These results highlight the relevance of visual-based health promotion strategies in strengthening hygiene literacy and behavioral outcomes in rural settings. Integrating visual education with environmental support systems may enhance the sustainability of hygiene practices at the community level.